Anti-Inflammatory and Antioxidant Properties of β-Sitosterol in Copper Sulfate-Induced Inflammation in Zebrafish (Danio rerio) - Peng Zhang; Naicheng Liu; Mingyang Xue; Mengjie Zhang; Wei Liu; Chen Xu; Yuding Fan; Yan Meng; Qinghua Zhang; Yong Zhou (MDPI AG, 2023)
β-Sitosterol, which is used extensively in pharmaceuticals, nutraceuticals, and cosmetics, has high nutritional value along with immunomodulatory and anti-inflammatory properties. In this study, we investigated the antioxidant and anti-inflammatory effects of β-sitosterol in zebrafish and explored the associated molecular mechanisms. In an in vivo antioxidant experiment, zebrafish (Danio rerio) larvae were treated with different concentrations of β-sitosterol and then exposed to a nonlethal concentration of CuSO4 to induce oxidative stress. Treatment with β-sitosterol at 70 or 100 μg/mL significantly reduced CuSO4-induced oxidative stress in the zebrafish, demonstrating the strong antioxidant activity of β-sitosterol. Treatment with β-sitosterol protected zebrafish larvae against oxidative damage from CuSO4 by upregulating the expressions of sod and gpx4b. In a zebrafish model of inflammation, pretreatment with β-sitosterol before CuSO4 exposure inhibited neutrophil recruitment and damage to lateral line neuromasts, indicating a potent anti-inflammatory effect derived from reductions in the expressions of il-8 and myd88. The results demonstrate the antioxidative and anti-inflammatory activities of β-sitosterol and suggest that β-sitosterol may be useful for the treatment of various inflammatory diseases.